Competitive Strategic Position Analysis of Publicly Listed Hospital Companies in Indonesia - Febrianto, Alvano; Kaltum, Umi (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2024)
In the rapidly evolving and highly competitive landscape of the hospital industry, analysing the strategic competitive position of the hospital is crucial in the process of strategic planning. This research evaluates the strategic competitive positions of 11 publicly listed hospital companies by performing a dynamic portfolio analysis starting in the 2020-2023 period, representing the most recent developments in the hospital sector in Indonesia. This research employs the BCG matrix technique, drawing on data related to the actual throughput of the hospital industry. This technique enables quantitative comparisons at the micro-level regarding hospitals' growth rates and market shares. The dynamic portfolio analysis findings indicated that Siloam Hospitals, Hermina Hospitals, and Mitra Keluarga Hospitals are well-performing companies with good positions in the industry. However, the results also revealed that some companies exhibited a negative trend in growth rate in terms of their competitive positions. By exploring a topic that has received limited attention from researchers, this research will contribute to the academic literature in defining the market structure of the hospital industry in Indonesia.